The genus Pediopsoides Matsumura (Hemiptera: Cicadellidae, Macropsini) from Mainland China, with description of two new species - Dai, Wu; Zhang, Yalin (Zootaxa, 2009)
Four species of the genus Pediopsoides Matsumura are recorded from Mainland China. Among them, Pediopsoides dilatus sp. nov. and Pediopsoides heterodigitatus sp. nov. are described as new, and Pediopsoides kurentsovi (Anufriev) is redescribed. One new combination, Pediopsoides aomians (Kuoh, 1981) comb. nov. (from Oncopsis) is proposed and two new synonyms are revealed, the genus Digitalis Liu and Zhang, 2002 (type species: Digitalis striolatus Liu and Zhang) is synonymised with Pediopsoides, Digitalis striolatus Liu and Zhang is a new junior synonym of Pediopsoides aomians (Kuoh). Images of adults and genitalia of the four species are provided, along with a checklist of the known species of the genus.